Design and synthesis of Cr2O3-ZrO2: tailoring properties of Pt/Cr2O3-ZrO2 via different Cr2O3 loading for cracking activity / N.H.R. Annuar ... [et al.] - Annuar, N.H.R.; Alias, A.F.N.; Yusoff, S.N.H.M.; Hairi, H.M.; Mohamad, S.N.; Jalil, A.A. (2020)
World-wide public concern about the earth’s environment and health considerations led into several new legislative action all around the world. Solid acid catalysts play a crucial role in the petrochemical industry, where they have largely replaced traditional acids active in the liquid phase for hydrocarbon transformations. Cr2O3-ZrO2 have been explored to improve the activity, selectivity and stability of catalyst. Cumene hydrocracking selected as a model reaction over Cr2O3-ZrO2 where this cracking has been reported to be a reaction for the simultaneous determination of Brønsted as well as Lewis acidity. The influence of the amount of Cr2O3 loading was studied in order to elucidate the effects and limitation of Cr2O3 loading on the properties and activity of Pt/Cr2O3-ZrO2. The results of IR studies and catalytic hydrocracking were demonstrated in order to clarify the relationship between Cr2O3 loading with the activity of Pt/Cr2O3-ZrO2 in the presence of hydrogen gas. The catalyst with 8 wt.% loading performed with a maximum activity in cumene hydrocracking at 523 K which due to presence of Cr=O band at 1035 cm-1 which extensively interacted with H2 to form protonic acid sites via a hydrogen spillover phenomenon.